POTENTIATION EFFECT OF VITAMIN E ON REDUCED DOSAGE OF OVAPRIM IN INDUCED SPAWNING OF Clarias gariepinus - Uka, A; Obijiaku , I. C. (Nigerian Journal of Fisheries, 2019)
A study was conducted to compare the fecundity, fertilization, hatchability and larval survival of Clarias gariepinus induced to spawn using ovaprim diluted by 20%, 30%, 40%, 50% and 0% with vitamin E. This was concomitant to administration of 0.4ml/kg, 0.35ml/kg, 0.30ml/kg, 0.25ml/kg and 0.5ml/kg ovaprim respectively to five groups of fish in three replicates. Water quality temperature, pH and dissolved oxygen (DO) were measured using digital metres during the study. There was significant difference (P<0.05) in egg production, fertilization, hatchability and larval survival among the treatments. Relative fecundity of 29.2g/kg, 36.8g/kg, 41.2g/kg, 43.4g/kg and 32.9g/kg was realized at 20%, 30%, 40%, 50% and 0% dilution respectively. Highest fertilization rate of 89.3% and best hatchability rate of 73.4% were recorded in fish induced at 50% dilution. Percentage survival of 75.4% and 73.4% recorded at 40% and 50% dilution respectively were significantly (P<0.05) higher than the rest including the control which recorded the lowest larval survival rate of 58.9%. There was no significant difference (P>0.05) in the water quality parameters among the experimental units. It was evident from the study that, adding vitamin E to generic ovaprim enhanced hormone potency of ovaprim and its efficiency in low dosage.